Deliberative Problems in the Distribution of Covid-19 Social Assistance: Critical Dialogue with the Village Government - Dadang Fredianto; Sholih Mu'adi; Anif Fatma Chawa (Journal of Governance, 2021)
The distribution of Covid-19 social assistance has caused vertical conflicts between the village government and its people. This problem occurred all over Indonesia, including in Blitar Regency, where the village heads gave up and asked for advocacy from the District Parliament (DPRD). This study aims to identify the problem in the distribution of Covid-19 social assistance faced by the village government in Blitar Regency. Critical paradigms are used as the basis for finding problems, while the research approach used is qualitative with a case study. The results showed that the problems in the distribution of Covid-19 Social Assistance in villages in Blitar Regency are divided into two, the accompanying problem in each social assistance and the derivative problem resulting from the social assistance distribution processes. Theoretically, most of the distribution of the covid-19 social assistance are experiencing deliberative problems which means the absence of deliberation. Elaboration on the recommendations made by the village government, the analysis of theories, and relevant studies refers to the alignment towards deliberative democratic methods, because this method hints at the management of social assistance that is more participatory, transparent, and oriented to the value of justice.